Optimization of microwave extraction process of essential oil from Perilla frutescens by response surface methodology and its chemical composition analysis - LIN Meng-nan; SU Ping; YING Li-ya; GAO Hong-jian (浙江大学学报. 农业与生命科学版, 2011)
The essential oil from Perilla frutescens were extracted by microwave method, and the optimum extraction conditions were obtained through response surface methodology, then the constituents of the essential oil were identified by gas chromatography-mass spectrometry (GC-MS), in the meantime, with scanning electron microscope (SEM), the damages of the cell structures were observed. The results showed that the optimum extraction condition was as follows: cyclohexane as solvent, microwave power of 329 W, irradiation time of 80 s, material to liquid ratio of 1∶6, soaking time of 56 min. Under the optimum extraction condition, the actual detection value of the essential oil was 1.783%, that was almost equal to the predictable value. Seventeen compounds, identified by means of GC-MS, made up 80.61% of the essential oil, whose main components were perillaldehyde (44.54%) and D-limonene (15.7%). Under the scanning electron microscope (SEM), the cell wall had little damage during the irradiation, but the cell membrane and mitochondria were badly damaged; although the outlines of several cellular organs were clear, including chloroplast and starch grain, they all had some contents effusing.